Tectonics in Architecture of Tanean Lanjhang and Osing House: The Impact on the Growth of Space Area - Catherine Kirsten Eka Wijaya; Agus Dwi Hariyanto; Phylicia Deosephine Soegiono; Eveelyn Febe Gunawan (DIMENSI (Journal of Architecture and Built Environment), 2024)
This research was initiated by an interest in vernacular architecture, which adapts to fit the changing demands of its inhabitants. Cultural variations and differing population demands can cause spatial planning patterns to vary even within a province or between nearby places. Tectonic formations are produced by the growth of vernacular houses. In addition to understanding the distinctive tectonic structures through the connections of elements in the expanded spaces, this study attempts to identify and classify the spatial arrangement patterns in the vernacular houses of Tanean Lanjhang and Osing. Tanean Lanjhang and Osing buildings are examples of vernacular architecture known as "grow houses," which have horizontal expansion as their principal growth criterion. The two kinds of houses, however, expand in different directions. This research uses qualitative techniques, such as literature reviews on Osing houses and on-site observations of Tanean Lanjhang houses. The results show that the Tanean Lanjhang houses show three orientations of spatial arrangement patterns: expansion in the middle, forward, and backward areas. Osing houses, on the other hand, extend from front to back. Both types of houses have connections built with or without gutters, despite the variations in the connections between each of the elements within them.